Endothelial Cullin3 Mutation Impairs Nitric Oxide-Mediated Vasodilation and Promotes Salt-Induced Hypertension. Issue 3 (8th April 2022) - Wu, Jing; Fang, Shi; Lu, Ko-Ting; Kumar, Gaurav; Reho, John J; Brozoski, Daniel T; Otanwa, Adokole J; Hu, Chunyan; Nair, Anand R; Wackman, Kelsey K; Agbor, Larry N; Grobe, Justin L; et al.
Abstract: Human hypertension caused by in-frame deletion of CULLIN3 exon-9 (Cul3∆9) is driven by renal and vascular mechanisms. We bred conditionally activatable Cul3∆9 transgenic mice with tamoxifen-inducible Tie2-CRE ERT2 mice to test the importance of endothelial Cul3. The resultant mice (E-Cul3∆9) trended towards elevated nighttime blood pressure (BP) correlated with increased nighttime activity, but displayed no difference in daytime BP or activity. Male and female E-Cul3∆9 mice together exhibited a decline in endothelial-dependent relaxation in carotid artery. Male but not female E-Cul3∆9 mice displayed severe endothelial dysfunction in cerebral basilar artery. There was no impairment in mesenteric artery and no difference in smooth muscle function, suggesting the effects of Cul3∆9 are arterial bed-specific and sex-dependent. Expression of Cul3∆9 in primary mouse aortic endothelial cells decreased endogenous Cul3 protein, phosphorylated (S1177) endothelial nitric oxide synthase (eNOS) and nitric oxide (NO) production. Protein phosphatase (PP) 2A, a known Cul3 substrate, dephosphorylates eNOS. Cul3∆9-induced impairment of eNOS activity was rescued by a selective PP2A inhibitor okadaic acid, but not by a PP1 inhibitor tautomycetin. Because NO deficiency contributes to salt-induced hypertension, we tested the salt-sensitivity of E-Cul3∆9 mice. While both male and female E-Cul3∆9 mice developed salt-induced hypertension and renal injury, the pressor effect of salt was greater in female mutants. The increased salt-sensitivity in female E-Cul3∆9 mice was associated with decreased renovascular relaxation and impaired natriuresis in response to a sodium load. Thus, CUL3 mutations in the endothelium may contribute to human hypertension in part through decreased endothelial NO bioavailability, renovascular dysfunction, and increased salt-sensitivity of BP. Graphical Abstract: